Effect of Marginal Designs on Fracture Strength of High Translucency Monolithic Zirconia Crowns - Niwut Juntavee; Sasiprapa Kornrum (International Journal of Dentistry)
Introduction. Monolithic zirconia is able to achieve certain aesthetic, but its durability in resisting fracture has been questioned, as fractures often originate from margins of restoration. This study determined fracture resistance of highly translucent monolithic zirconia crowns with different margin designs in terms of marginal thickness and collar height. Materials and Methods. Zirconia blanks (Ceramill® Zolid HT+) were selected for the fabrication of zirconia crowns according to different designs, including varying margin thicknesses (light chamfer, CL; heavy chamfer, CH) and collar heights (no collar, NC; low collar, LC; high collar, HC), which resulted in CLNC, CLLC, CLHC, CHNC, CHLC, and CHHC groups (15 crowns each). The crowns were seated on a metal die and loaded vertically through round end punch (θ = 10 mm), contacting with inclined planes of cusp in a testing machine with crosshead speed of 0.2 mm/min until fracture. Videos with a rate of 50 frames/second were used to record fracture. Fracture load (N) and durable period (s) were compared for significant differences using ANOVA and Bonferroni test (α = 0.05). Results. The mean ± sd of fracture load (N) and durable time (s) were 3211 ± 778 and 212 ± 47 for CLNC; 3041 ± 1370 and 188 ± 53 for CLLC; 2913 ± 828 and 192 ± 27 for CLHC; 4226 ± 905 and 245 ± 35 for CHNC; 4486 ± 807 and 228 ± 29 for CHLC; and 4376 ± 1043 and 227 ± 37 for CHHC. This indicated that marginal thickness had a significant influence on load-bearing capacity and durable time (p<0.05). No significant impact of collar height was shown, either on load-bearing capacity or durable time (p>0.05). No interaction between two factors was presented (p>0.05). Conclusions. Heavy chamfer margin provided stronger zirconia crown than light chamfer, but both were capable of withstanding fracture load higher than maximum masticatory force. Neither presence nor absence of collar indicated any impact on strength. Fabrication of zirconia crowns with either heavy or light chamfer margin and either presence or absence of collar, with the consideration of emergence profile, should be considered.